(untitled) (Хабаршы. Психология және социология сериясы, 2020)
In the current situation of increasing geopolitical turbulence, the development of means to counter the methods of destabilizing the socio-political situation (the so-called “orange revolutions”) is an extremely important task. The purpose of this work is to prove the fact that methods of counteracting the “orange revolutions” can be associated with the educational process on the basis of new information technologies, as well as the development of principles on which appropriate educational technologies can be built. The methodology is based on identifying people from the youth environment who are capable of one or another activities (both in a constructive and destructive way) and reorienting them to solving actual scientific problems of interdisciplinary nature. The paper describes the results of the primary experiment based on writing critical reviews for pseudoscientific works by undergraduates and it has been shown that this kind of testing meets the task. It has been shown that this monitoring method is more promising than attempts to monitor the psycho-emotional state of young people in digital social networks. It has been shown that this method is well combined with the method of monitoring professional and other inclinations based on the active interaction of the reader with interactive tutorials that was proposed earlier. These methods make it possible to comprehensively solve the problem of the preventive orientation of persons capable to vigorous activity in a constructive direction (the output of passionary energy into scientific creativity), which significantly reduces the personnel base for the initiators of the “orange revolutions”. Key words: geopolitical turbulence, passionarity, information war, pseudoscience, destructive entrepreneurship.